Implementasi Metode Sha-12 Untuk Mendeteksi Orisinalitas File Video - Siregar, Serdima (Buletin Ilmiah Informatika Teknologi, 2024)
As times progress, and supported by very rapid technological developments, especially for producing video files, currently producing video files is very easy with various brands of cellphones and there are many models of cameras that can be used to record video, which almost everyone has. person. Video is one of the data representation objects that has been processed. The form of video data is the result of combining images and sound. Video media can also be interpreted as a set of components or media that is capable of displaying images and sound at the same time. The SHA-512 cryptography method produces a 512 bit digest using iteration over a 1024 bit message block. The SHA-512 algorithm includes a hash function that produces the longest hash value, namely 512 bits.)